The Prospects of Cooperation with China - S. Kizima (Евразийская интеграция: экономика, право, политика, 2019)
May visit of Xi Jinping to Kazakhstan; Russia and Belarus has been associated with the implementation of different interests of the elites of these countries. Russia and Belarus have acute interest in the development of relations with China because of economic and financial problems strengthened against the background of Ukrainian crisis; Kazakhstan’s position is more favorable. At the same time different interests of the elites of the three countries that were attended by Xi Jinping, will not prevent China from implementing the strategy outlined in the framework of the economic belt of the Silk Road.